Utilizing simulation in community health nursing education: a scoping review of current trends and applications - Zainab Al Kindi; Wafa Al Jabri; Manal Al Zadjali; Joshua Muliira (BMC Nursing)
Abstract Background Simulation-based education has been widely adopted in nursing education; however, its application in community and public health remains underexplored. As healthcare delivery continues to shift from hospital-based to community-based settings, and with the growing shortage of clinical placements, integrating innovative simulation strategies is essential to prepare students for population-level care. Objective This scoping review aimed to map the existing literature on the use of simulation in undergraduate community and public health nursing education, identify commonly used simulation modalities, and explore the learning outcomes associated with these approaches. Methods A scoping review was conducted following the Arksey and O’Malley (Arksey, Int J Multiling social research methodology 8, 2005) framework. A systematic search was carried out across six electronic databases, PubMed, CINAHL, PsychINFO, MEDLINE, ERIC, and EMBASE, to identify both published and unpublished studies. Reference lists and grey literature were also screened from November 2024 to January 2025. Consistent with scoping-review methodology, formal risk-of-bias appraisal was not undertaken, but study design and reporting quality were charted descriptively. Data were extracted, charted, and summarized narratively. Results A total of 2,327 articles were retrieved. After screening and applying eligibility criteria, 34 studies were included for full-text review and final analysis, with a total of 3,498 community/public health students participated in simulation activities, with individual study sample sizes ranging from 16 to 519 participants. High-fidelity simulation emerged as the most frequently utilized modality in community health nursing education. Additionally, several innovative approaches, including virtual reality, standardized patients, and telehealth simulations, were identified as promising strategies to enhance student engagement and clinical preparedness. The simulation topics addressed in the reviewed studies ranged from home visits and vaccine administration to poverty simulation and disaster preparedness, reflecting the breadth of community health nursing roles. Different simulation methods were associated with improved knowledge, communication skills, critical thinking, and perceived readiness for community-based practice. Conclusion The findings of this review highlight the growing integration of simulation in undergraduate community and public health education. While high-fidelity simulation remains predominant, the adoption of innovative strategies offers new opportunities to align educational practices with evolving public health priorities. Future research should focus on evaluating the impact of these modalities on long-term learning outcomes and practice readiness. Clinical trial number Not applicable.